Influences and Optimizations of Vertical Facades on the Aerodynamic Loadings for High-Rise Buildings - Xu Cheng; Guoqing Huang; Bowen Yan; Qingshan Yang; Chao Wang; Bo Li; Shuguo Liang (Buildings)
The architectural facade, including balconies, vertical frames, and sunshades, is widely installed on the surfaces of high-rise buildings, and will affect the wind load and airflow around the buildings. However, current studies mainly focus on local wind pressure, with limited research on aerodynamic forces and a lack of optimization design methods for vertical facades. This paper investigates the aerodynamic effects of different vertical facade layouts on high-rise buildings through wind tunnel experiments. Subsequently, CFD simulations were performed on 120 generated models. By combining neural networks and genetic algorithms, this paper optimized the aerodynamics of the vertical facades on a high-rise building, analyzed the flow field around the building, and provided reference for the aerodynamic optimization design of vertical facades on high-rise building facades. The results show that vertical facades could reduce the base shear forces and overturning moments of tall buildings, and the mean drag coefficient can be reduced by up to 31%, and the RMS value of lateral force coefficient by 57%, through the aerodynamic optimization. Through the analysis of flow fields around tall buildings, the “chamfer” formed by the vertical facades and the building corner is attributed as the main reason for reducing the aerodynamic forces of tall buildings. Furthermore, the negative resistance on vertical facades caused by the adverse pressure gradient is another major factor for reducing the mean value of aerodynamic force.